Computer-based cognitive rehabilitation: the CoRe system. Issue 4 (13th February 2017) - Alloni, Anna; Sinforiani, Elena; Zucchella, Chiara; Sandrini, Giorgio; Bernini, Sara; Cattani, Barbara; Pardell, Daniela Tost; Quaglini, Silvana; Pistarini, Caterina
Abstract: Purpose : This work aims at providing a tool for supporting cognitive rehabilitation. This is a wide field, that includes a variety of diseases and related clinical pictures; for this reason the need arises to have a tool available that overcomes the difficulties entailed by what currently is the most common approach, that is, the so-called pen and paper rehabilitation. Methods : We first organized a big number of stimuli in an ontology that represents concepts, attributes and a set of relationships among concepts. Stimuli may be words, sounds, 2D and 3D images. Then, we developed an engine that automatically generates exercises by exploiting that ontology. The design of exercises has been carried on in synergy with neuropsychologists and speech therapists. Solutions have been devised aimed at personalizing the exercises according to both patients' preferences and performance. Results : Exercises addressed to rehabilitation of executive functions and aphasia-related diseases have been implemented. The system has been tested on both healthy volunteers ( n = 38) and patients ( n = 9), obtaining a favourable rating and suggestions for improvements. Conclusions : We created a tool able to automate the execution of cognitive rehabilitation tasks. We hope the variety and personalization of exercises will allow to increase compliance, particularly from elderly people, usually neither familiar with technology nor particularly willing to rely on it. The next step involves the creation of a telerehabilitation tool, to allow therapy sessions to be undergone from home, thus guaranteeing continuity of care and advantages in terms of time and costs for the patients and the National Healthcare System (NHS). Implications for rehabilitation: Cognitive impairments can greatly impact an individual's existence, appreciably reducing his abilities and autonomy, as well as sensibly lowering his quality of life. Cognitive rehabilitation can be used to restore lost brain function or slow down degenerative diseases. Computerization of rehabilitation entails many advantages, but patients – especially elderly people – might be less prone to the use of technology and consequently reluctant towards this innovative therapeutic approach. Our software system, CoRe, supports a therapist during the administration of rehabilitation sessions: exercises can be generated dynamically, thus reducing repetitivity, and patients' performance trends automatically analysed to facilitate the assessment of their progress. Tests performed on both healthy subjects and patients provided useful information that allowed us to define an implementation strategy able to reduce patients' resistance to computerized rehabilitation as much as possible.